Emotional expression in human odour - Roberts, S Craig; Třebická Fialová, Jitka; Sorokowska, Agnieszka; Langford, Ben; Sorokowski, Piotr; Třebický, Vít; Havlíček, Jan (Evolutionary human sciences, 2022)
Recent work has demonstrated that human body odour alters with changing emotional state and that emotionally laden odours can affect the physiology and behaviour of people exposed to them. Here we review these discoveries, which we believe add to a growing recognition that the human sense of smell and its potential role in social interactions have been underappreciated. However, we also critically evaluate the current evidence, with a particular focus on methodology and the interpretation of emotional odour studies. We argue that while the evidence convincingly indicates that humans retain a capacity for olfactory communication of emotion, the extent to which this occurs in ordinary social interaction remains an open question. Future studies should place fewer restrictions on participant selection and lifestyle and adopt more realistic experimental designs. We also need to devote more consideration to underlying mechanisms and to recognise the constraints that these may place on effective communication. Finally, we outline some promising approaches to address these issues, and raise some broader theoretical questions that such approaches may help us to answer.
Keywords: odor; olfaction; fear; communication; smell